2018
DOI: 10.1111/jcmm.13641
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell‐derived conditional medium promotes Leydig cell anti‐apoptosis and proliferation via autophagy and Wnt/β‐catenin pathway

Abstract: Leydig cell transplantation is a better alternative in the treatment of androgen‐deficient males. The main purpose of this study was to investigate the effects of induced pluripotent stem cell‐derived conditioned medium (iPS‐CM) on the anti‐apoptosis, proliferation and function of immature Leydig cells (ILCs), and illuminate the underlying mechanisms. ILCs were exposed to 200 μmol/L hydrogen peroxide (H2O2) for 24 hours with or without iPS‐CM treatments. Cell apoptosis was detected by flow cytometric analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Moreover, Leroux et al (48) reported that MScs, via the Wnt4 pathway, improved skeletal muscle fiber regeneration following ischemic injury. Other studies have also demonstrated activation of the Wnt pathway by MScs (55)(56)(57). The present study found that, in the presence of hdPSc-cM, the levels of Wnt/β-catenin pathway-related proteins, including p-GSK-3β and β-catenin, were upregulated.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, Leroux et al (48) reported that MScs, via the Wnt4 pathway, improved skeletal muscle fiber regeneration following ischemic injury. Other studies have also demonstrated activation of the Wnt pathway by MScs (55)(56)(57). The present study found that, in the presence of hdPSc-cM, the levels of Wnt/β-catenin pathway-related proteins, including p-GSK-3β and β-catenin, were upregulated.…”
Section: Discussionsupporting
confidence: 72%
“…In our recent study, we observed autophagy induced by TiO 2 NPs in mesenchymal stem cells (MSCs) originating from the bone marrow of humans [ 26 ]. While the role of autophagy in determining cell death or survival is dependent on the internal and external environment and cell type [ 25 ], autophagy has also been known to be related with the Wnt/GSK3β/β-catenin pathway [ 27 ], which is a classic promoter of cell proliferation [ 28 ] and has been regarded as a participant in the maintenance of homeostasis via cell-cell communication [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxidative species (ROS) level was measured with the fluorescence dye 2’7’-dichlorofluorescin diacetate (DCFH-DA) as previously described (Guo et al, 2018). Briefly, 1.5 × 10 5 cells/ml rat immature Leydig cells were seeded into a six-well plate and cultured in 34°C and 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Immature Leydig cells were seeded into a 12-well plate with the density of 5 × 10 5 cells/well and cells were incubated with propofol (0, 5, and 50 µM) for 3 h. To evaluate early and late apoptosis, an Annexin V-FITC/PI Kit was used as previously described (Guo et al, 2018). Cells were harvested and washed with cold PBS and resuspended in 200 µl of Annexin V-binding buffer.…”
Section: Methodsmentioning
confidence: 99%